Building character in madrasah: The role of educational punishment for lower grade students – A literature review - Tubagus Syihabudin; Siti Ngaisah; Eneng Muslihah (Pelita International Publishing, 2025)
Character instilling in students is the primary mandate of education in Indonesia, including in madrasah that combine general and religious education. One of the popular strategies in character formation in the madrasah environment is the application of educational punishment. The punishment to shape the character of lower-class students still causes controversy among educators, parents, and education experts. The study reviewed the literature on the role and effectiveness of educational punishment in shaping the character of madrasah students, with a focus on lower-class students. The method used is a literature study with descriptive analysis of the results of previous research and related policies. Research findings show that educational punishment is still commonly used in lower-class madrasah, employed through various methods. Educational punishment in the form of self-reflection and social tasks is effective in instilling discipline and responsibility in students. Physical punishment or humiliation has negative impacts, including fear, aggressiveness, and a decreased interest in learning. Positive discipline based on religious values is more effective, but its implementation is less consistent in the field. Further research on the wise application of educational punishment can reinforce students’ character. It is crucial to uphold humanistic principles and consider the psychological development of children.